QUALITATIVE STUDY EXPERIENCE EXTENDED FAMILY IN CHILD CARE IN TEENAGE COUPLES IN GUNUNGKIDUL REGENCY - Asti Ratnaningrum; Warsiti Warsiti; Endang Koni Suryaningsih (Jurnal Endurance, 2025)
Background : The unpreparedness of teenage couples to become parents often results in deviant child rearing in the form of physical violence, psychological violence, and sexual violence. Most teenage couples live with extended families who are involved in parenting. Aim : Obtaining an in-depth picture of the extended family's experience in supporting childcare for teenage couples. Method: Qualitative research with a phenomenological approach. Informants in the study were selected using purposive sampling techniques. Triangulation of research data using three sources, namely from extended families, teenage couples and midwives. Data collection techniques using in-depth interviews and FGDs. Method Qualitative research with a phenomenological approach. Informants in the study were selected using purposive sampling techniques. Triangulation of research data using three sources, namely from extended families, adolescent couples and midwives. Data collection techniques with in-depth interviews and FGDs. Results : This study obtained 5 themes, namely the knowledge of extended families about parenting children of adolescent couples is already comprehensive, perceptions and expectations of extended families towards parenting children in adolescent couples, extended families are significant others for adolescent couples in the perinatal period, involvement of extended families in health services is to help in childcare, provide education related to childcare patterns although there are also differences with adolescent couples regarding childcare patterns that influence decision making. The fifth theme, extended families are a simple way to detect child growth and development, modern parenting patterns and early treatment of sick infants and toddlers. Conclusion: Differences in parenting patterns of extended families and teenage couples require support from health workers in providing appropriate education on child care according to the child's age. Teenage couples are expected to be more mature and responsible in raising children Keywords: extended family; parenting ; adolescent couples; sexual violence